Influences of Sensor Placement Site and Subject Posture on Measurement of Respiratory Frequency Using Triaxial Accelerometers - Hughes, Stephen; Liu, Haipeng; Zheng, Dingchang (Frontiers in Physiology, 2020)
Introduction Respiration frequency (RF) could be derived from the respiratory signals recorded by accelerometers which detect chest wall movements. The optimum direction of acceleration for accurate RF measurement is still uncertain. We aim to investigate the effect of measure site, posture, and direction of acceleration on the accuracy of accelerometer-based RF estimation. Methods Respiratory signals were measured from 34 healthy subjects in 70 seconds by triaxial analogue accelerometers located at four sites on the body wall (over the clavicle, laterally on the chest wall, over the pectoral part of the anterior chest wall, on the abdomen in the midline at the umbilicus). The reference respiratory signal was simultaneously recorded by a strain gauge chest belt. Measurements were repeated at rest state in supine and seated postures. RFs were extracted from the accelerometer-based and reference respiratory signals using wavelet transformation. To investigate the effect of measure site, posture, and direction of acceleration on the accuracy of accelerometer-based RF estimation, repeated measures multivariate analysis of variance, linear regression, and Bland-Altman analysis were performed between reference and accelerometer-based RFs. Scheirer-Ray-Hare test was performed on the error of accelerometer-based RF which was defined as the difference between corresponding RF-based and reference RF values. Results There was no significant difference in accelerometer-based RF estimation between seated and supine postures, among four accelerometer sites, or between seated or supine postures (p>0.05 for all). The error of accelerometer-based RF estimation was less than 0.03Hz (two breaths per minute) at any site or posture, but was significantly smaller in supine posture than in seated posture (p<0.05), with narrower limits of agreement in Bland-Altman analysis and higher accuracy in linear regression (R square>0.61 vs R square<0.51). Conclusion RF can be accurately measured from the acceleration of any direction using triaxial analogue accelerometers placed at the clavicular, pectoral and lateral sites on the chest as well the mid abdominal site. More accurate RF estimation could be achieved in supine posture compared with seated posture.